2020
DOI: 10.1371/journal.pone.0243584
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of finite population distribution function with dual use of auxiliary information under non-response

Abstract: In this paper, we propose two new families of estimators for estimating the finite population distribution function in the presence of non-response under simple random sampling. The proposed estimators require information on the sample distribution functions of the study and auxiliary variables, and additional information on either sample mean or ranks of the auxiliary variable. We considered two situations of non-response (i) non-response on both study and auxiliary variables, (ii) non-response occurs only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…is the multiple correlation coefficient of y h on 􏽢 V h and 􏽢 X h . Now by putting different values of K ih in (28), some members of the proposed class of estimators can be obtained as…”
Section: Snomentioning
confidence: 99%
See 1 more Smart Citation
“…is the multiple correlation coefficient of y h on 􏽢 V h and 􏽢 X h . Now by putting different values of K ih in (28), some members of the proposed class of estimators can be obtained as…”
Section: Snomentioning
confidence: 99%
“…Singh et al [26] considered the problem of estimating the DF and quantiles with the use of auxiliary information at the estimation stage of a survey. Moreover, Yaqub and Shabbir [27], Hussain et al [28], and Hussain et al [29] considered a generalized class of estimators for estimating the DF in the presence of non-response, while Hussain et al [30] proposed two new families of estimators using dual auxiliary information under simple and stratified random sampling. Furthermore, Ahmad et al [31] suggested a new estimator of DF using auxiliary information.…”
Section: Introductionmentioning
confidence: 99%
“…Kuk [7] presented a classical as well as a prediction approach in estimating the distribution function from a survey data. Researchers can investigate articles related to distribution function (DF) such as research studies conducted by Chamber et al [8]; Dorfman [9]; Diana [10]; Rao [11]; Diana and Perri [12]; Ahmad and Abu-Dayyeh [13]; Rueda and Arcos [14]; Singh and Kumar [15]; Dorfman [16]; Diana and perri [12]; Husaain et al [17]. ey proposed two new estimators for estimating the finite population distribution function based on simple and stratified random sampling schemes using supplementary information.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of the non-response, the study population is assumed to be stratified into two strata. The response and the non-response variable [5]. Considering a study variable of size N, i=1,2…, N. we suppose there are two strata of the study population, the response stratum of size and the nonresponse stratum of size .…”
Section: Introductionmentioning
confidence: 99%